Body composition in metabolic syndrome: Proposal of a protocol for a randomized clinical trial evaluating the effect of whole-body vibration exercise - Reis, Aline S.; Paineiras-Domingos, Laisa L.; Moreira-Marconi, Eloá; Moura-Fernandes, Márcia C.; Quinart, Hervé; Boyer, François Constant; Neves, Mario Fristh; Taiar, Redha; Bernardo-Filho, Mario; Sá-Caputo, Danúbia C. (Brazilian Journal of Health and Biomedical Sciences, 2019)
Introduction: Metabolic syndrome (MetS) is characterized by a group of cardiovascular risk factors, such as hypertension, hyperglycemia, hypercholesterolemia, low high-density cholesterol and increased abdominal fat. Over the years, changes in body composition occur, with accelerated loss of lean mass and increased fat mass, favoring cardiometabolic disorders. A strong relationship exists between physical inactivity and the presence of multiple risk factors for MetS. Thus, physical exercise has been recommended for the prevention of cardiovascular, chronic and MetS diseases. Whole-body vibration (WBV) exercise can be considered to be an exercise modality that benefits the muscular strength and cardiovascular health of elderly, sick and healthy people. Individuals with MetS are unmotivated to perform physical exercise regularly and, therefore, new approaches to intervention for this population are desirable. Objectives: The aim of this study is to present a protocol to verify the effect of WBV exercise on the body composition of MetS individuals. Methods: Randomized controlled trial with MetS individuals that will be allocated to an intervention group (WBVG) and a control group (CG). Participants will be placed barefoot on the base of a side alternating vibrating platform, with 130º knee flexion. Individuals (WBVG and CG) will perform the protocol for 12 weeks, twice a week. The CG subjects will perform the exercises at 5Hz throughout the intervention and those from the WBVG will perform the 5Hz exercises in the first session, adding 1Hz per session, ending the protocol at 16Hz. The body composition will be evaluated before and after the protocol using bioelectrical impedance analysis. Discussion: Studies involving WBV exercise have shown improvement in composition in individuals with different conditions (healthy and unhealthy). Conclusion: The proposed protocol will permit the acquisition of findings that will be relevant in the evaluation of the effect of the WBV on the body composition of MetS individuals due to its ease of realization, low cost and safety. Keywords: Whole body vibration exercise; Metabolic syndrome; Physical activity.